Predicting the age of sardine juveniles (Sardina pilchardus) from otolith and fish morphometric characteristics - Silva, Andreia V.; Meneses, Isabel; Silva, Alexandra (Scientia Marina, 2015)
An age prediction model based on individual morphometric characteristics (total length; weight) and otolith morphometric characteristics (diameter; weight) was investigated for juvenile sardine, Sardina pilchardus (Walbaum, 1792). Juveniles were collected from northern Portugal between May 2004 and January 2005. Daily growth rings were counted on the otoliths of 114 juveniles of 7-16 cm total length. The sample was divided into a training sample used to develop the age prediction model and a test sample used to evaluate the predictive ability of the model. The best model for predicting the logarithm of age was a linear regression with otolith diameter. The prediction of daily age was more accurate for younger ( < 200 days) juveniles. Overall, ages predicted from the model were unbiased in relation to ages determined from otolith microincrement counts. Moreover, predicted daily ages reproduced the overall shape of the observed age distribution and provided comparable growth estimates (0.041 cm day–1). The back-calculated birthdate period ranged from 29 September 2003 to 22 July 2004, with a peak in January 2004, which is consistent with the spawning season. The model presented here could be used as a method for increasing the volume of juvenile daily age data. Since growth and survival varies spatially and temporally, relationships between age and otolith/fish morphometry should not be extrapolated outside sampled periods, areas and fish size/age.